Thariqah-Based Neck Exercise Program Reduces Headache Intensity Among Indonesian College Students - Sukarmin, Sukarmin; Nurachmah, Elly; Yona, Sri; Gayatri, Dewi; Rochana, Nana (Nurse Media Journal of Nursing, 2024)
Background: Headaches are common among students due to academic stress and poor sleep habits. One way to reduce headaches is through neck exercises using Thariqah movements. Previous studies have focused only on physical neck exercises, yet a more holistic approach by combining dzikr (Laa ilaha ilallah) recited Thariqah movements with the exercises has never been studied.Purpose: This study aimed to determine the impact of Thariqah-based neck exercises on headache intensity experienced by college students.Methods: The study used a two-arm parallel randomized controlled trial design. College nursing students were recruited through purposive sampling and then sequentially randomized, with 64 respondents in each group. Participants in the intervention group performed Thariqah-based neck exercises during dzikr three times per week for three weeks, while those in the control group received educational leaflets on headache management. Headache intensity was measured using the Numeric Pain Scale (0-10 scale). Data were analyzed using the Wilcoxon and Mann-Whitney tests.Results: The results showed that Thariqah-based neck exercises performed during dzikr had a significant effect on reducing headache intensity among students (p= 0.000). The differences in headache intensity before and after the intervention were also significant between the intervention and control groups (p=0.000).Conclusion: Neck exercises based on Thariqah movements accompanied by dzikr recitation may serve as a practical option for self-therapy or complementary therapy in managing mild to moderate headache complaints. The integration of physical and spiritual elements offers potential benefits for both physical relief and emotional well-being.